Microbiomes associated with saxicolous lichens inhabiting montane rocks in western Japan - Zichen He; Qi Liu; Takeshi Naganuma (Academia Biology)
The diversity and structure of bacterial populations associated with saxicolous lichens in western Japan were investigated by a microbiomic approach based on the V3–V4 region of bacterial 16S rRNA gene sequences. A total of six saxicolous lichens were collected. The mycobionts of the six lichens were affiliated with two species of Umbilicaria, while the photobionts were ascribed to one species of Trebouxia, both being well-known lichen-forming fungal and green algal genera, based on their 18S rRNA gene sequences. Based on the associated bacterial V3–V4 sequences, operational taxonomic units (OTUs) were generated and used for microbiomic analysis. The associated microbiomes were clustered mainly by the host fungal species. Comparison with the previously studied microbiomes of the Antarctic and Alpine saxicolous lichens, consisting of other Umbilicaria and Trebouxia species, showed a distinct separation among the lichen-associated microbiomes from Japan, Antarctica, and Alpine. The clearly identified biomarker OTUs at the phylum rank were affiliated with Acidobacteriota and Planctomycetota for Japan, Actinomycetota and Bacteroidota for Antarctica, and Pseudomonadota for Alpine based on relative V3–V4 abundances (and thus variable depending on V3–V4 sources). It was unclear whether the microbiomes and biomarkers were more affected by biogeographic (bioclimatic) features or Umbilicaria species. Nevertheless, this study was the first to reveal Umbilicaria-associated microbiomes in Japan and provided a basis for further investigations on other Umbilicaria and non-Umbilicaria lichen sources.